Problems and Prospects of Infrastructure and Innovative Development of Kazakhstan - Zhansaya Fazylova (International Journal of Engineering and Management Research, 2019)
This article is devoted to the research of solving the problems of innovative development and infrastructure of Kazakhstan. The article presents many examples of the development of innovation from foreign countries and a comparison with the current situation in Kazakhstan. The main problems in the development of innovative industry are identified and appropriate solutions and recommendations are proposed. In order to accelerate the slow development of economic growth in this area, the article raises the issues of attracting investment, the development of high-tech technologies, the elimination of technological backwardness, the development of the scientific sector, as well as issues of financing.